2017
DOI: 10.1002/uog.16009
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal follow‐up of levator ani muscle avulsion: does a second delivery affect it?

Abstract: The risk of developing new LAM avulsion after a second vaginal delivery is low (0.9%). Healing of LAM avulsion was observed in 13% of women who had at least one vaginal delivery. At 3-5 years after delivery, women with LAM avulsion reported symptoms of SUI more often than did those without, and had higher UDI and POPDI scores, implying more bothersome symptoms. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 30 publications
(83 reference statements)
1
25
0
1
Order By: Relevance
“…Most of the partial eta squares were above 0.06 or even 0.14, which represents moderate or even large effect size, respectively. Previously, we reported that no difference was observed in symptoms of pelvic floor disorders or pelvic floor health-related quality of life in women with LAM avulsion at 1 year after their first delivery 9,19 . However, at 3-5 years after the first delivery, even though there was no significant increase in LAM avulsion, more women with LAM avulsion reported symptoms of stress urinary incontinence.…”
Section: Discussionmentioning
confidence: 79%
“…Most of the partial eta squares were above 0.06 or even 0.14, which represents moderate or even large effect size, respectively. Previously, we reported that no difference was observed in symptoms of pelvic floor disorders or pelvic floor health-related quality of life in women with LAM avulsion at 1 year after their first delivery 9,19 . However, at 3-5 years after the first delivery, even though there was no significant increase in LAM avulsion, more women with LAM avulsion reported symptoms of stress urinary incontinence.…”
Section: Discussionmentioning
confidence: 79%
“…Differences in these parameters between VM and rest represent BN mobility; larger differences indicate more obvious BN activity and weaker pelvic floor support. Levator ani muscle trauma may lead to a larger width of the HA, particularly its anterior part ( Svabik, Shek & Dietz, 2009 ), which has been found to be associated with the development of UI ( Chan et al, 2017 ). A larger β angle and HA both at rest and VM; a larger α angle, γ angle, and BNVP at VM; and a larger BND have also been found in pregnant women with UI than without UI, even after adjustment for the influence of gestational weeks, which is important because UI symptoms are more likely to occur in the last than first trimester of pregnancy ( Wesnes, Hunskaar & Rortveit, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Другой, более реальной причиной и доказанным фактором риска десценции тазовых органов являются влагалищные роды [43] и акушерские травмы тазового дна [44]. Распространенность перинеального травматизма, по разным данным, составляет 6,5-85% [45].…”
Section: гинекологияunclassified